The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/ijc.23180
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‐3 expression is a marker for neuroblastic tumor maturation and is down‐regulated by MYCN

Abstract: Neuroblastoma and ganglioneuroma are neuroblastic tumors originating from the developing sympathetic peripheral nervous system. Ganglioneuromas are usually benign, while neuroblastomas have a variable prognosis and include very aggressive tumors. Examples exist of neuroblastomas regressing to ganglioneuromas and ganglioneuromas progressing to neuroblastomas. Little is known of the molecular differences between the tumor types. Here we report that Dickkopf-3 (DKK3), a putative extra cellular inhibitor of the Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 57 publications
5
41
0
Order By: Relevance
“…Wnt Agonist 1 treatment led to altered morphology and neuroblastoma cell fate resulting in apoptosis. Although some studies have shown links between Wnt signaling and neuroblastoma patient outcome (50)(51)(52), relatively few Wnt-neuroblastoma studies appear in the literature when compared with other major signaling pathways. mRNAseq profiling of neuroblastoma cell lines (unpublished) and "gene expression profiling of tumor samples" (personal communication S. Bulashevska, University of Bonn, Bonn, Germany and DKFZ, 11-06-13) is confirming that Wnt signaling components are altered in poor prognosis neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt Agonist 1 treatment led to altered morphology and neuroblastoma cell fate resulting in apoptosis. Although some studies have shown links between Wnt signaling and neuroblastoma patient outcome (50)(51)(52), relatively few Wnt-neuroblastoma studies appear in the literature when compared with other major signaling pathways. mRNAseq profiling of neuroblastoma cell lines (unpublished) and "gene expression profiling of tumor samples" (personal communication S. Bulashevska, University of Bonn, Bonn, Germany and DKFZ, 11-06-13) is confirming that Wnt signaling components are altered in poor prognosis neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have revealed that the downregulation of Dkk3 in cancer was a result of epigenetic silencing by DNA methylation (17). It also has been reported that transfection of Dkk3 in certain tumor cells affected their invasive capacity and led to cell apoptosis, indicating that Dkk3 may act as a tumor suppressor (14,32,34,39,40). However, Dkk3 mutant mice showed no enhanced tumorigenesis (41).…”
Section: A B C Dmentioning
confidence: 99%
“…Expression profiling of neuroblastic tumours and cell lines for the different Wnt family genes showed that both the canonical Wnt3a and the non-canonical Wnt5 were strongly expressed and that they could activate upstream Wnt signalling in neuroblastoma cells by phosphorylating the dishevelled co-receptor DVL3 (Revet et al, 2010). The importance of DKK3 in neuroblastoma was already shown in previous reports, in which DKK3 was implicated as a marker for neuroblastic tumour maturation and was shown to be down-regulated by MYCN (Bell et al, 2007;Koppen et al, 2008). Additionally, β-catenin has been shown to be strongly expressed and aberrantly localised in the nucleus in high-risk neuroblastoma cells without MYCN amplification (Liu et al, 2008).…”
Section: Chibbymentioning
confidence: 63%